2023
DOI: 10.3390/ijerph20095638
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID Symptoms in Occupational Cohorts: Effects on Health and Work Ability

Abstract: Post-acute COVID-19 syndrome is frequently observed in workers and has a substantial impact on work ability. We conducted a health promotion program to identify cases of post-COVID syndrome, analyze the distribution of symptoms and their association with work ability. Of the 1422 workers who underwent routine medical examination in 2021, 1378 agreed to participate. Among the latter, 164 had contracted SARS-CoV-2 and 115 (70% of those who were infected) had persistent symptoms. A cluster analysis showed that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
(67 reference statements)
1
9
0
1
Order By: Relevance
“…The results align with previous findings, confirming the significant psychosocial burden of PCS on patients' quality of life [18][19][20][21] . GP's observations of symptoms are broadly consistent with the current literature [22][23][24][25] .…”
Section: Comparison With the Existing Literaturesupporting
confidence: 83%
“…The results align with previous findings, confirming the significant psychosocial burden of PCS on patients' quality of life [18][19][20][21] . GP's observations of symptoms are broadly consistent with the current literature [22][23][24][25] .…”
Section: Comparison With the Existing Literaturesupporting
confidence: 83%
“…Returning to work is possible if daily activities are manageable and 500 m can be walked symptom-free. Work intensity should be discussed with the employer and other restrictions may apply, e.g., avoiding night shifts ( Magnavita et al, 2023 ). Moreover, physicians should discuss with their patients if their cognitive impairment may be a safety issue for professional or leisure activities, particularly for driving or operating machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Although PCS can develop in patients of all ages, the highest percentage of diagnoses is observed in patients between 36 and 50 years of age, which could impact on work productivity through an increased absence from work (absenteeism) ( Davis et al, 2023 ). A 2021 retrospective cross-sectional study with 1,378 employees undergoing their annual medical check-up in Italy found that PCS was associated with reduced ability to work ( Magnavita et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a grupo profesional, se observaba una mayor afectación de COVID Persistente en los trabajadores asistenciales (en primera línea de actuación sanitaria, más expuestos a la infección por Sars-CoV-2 en este período), versus los no asistenciales. La sintomatología de COVID Persistente más prevalente fue: afectación del sueño, pérdida de memoria, dificultades de concentración, cambios en el estado de ánimo, artralgias, fatiga y cefalea, observados en otros estudios de COVID Persistente (30)(31)(32)(33).…”
Section: Discussionunclassified